Active cargo loading into extracellular vesicles: Highlights the heterogeneous encapsulation behaviour. Issue 13 (31st October 2021) - Chen, Chaoxiang; Sun, Mengdi; Wang, Jialin; Su, Liyun; Lin, Junjie; Yan, Xiaomei
Abstract: Extracellular vesicles (EVs) have demonstrated unique advantages in serving as nanocarriers for drug delivery, yet the cargo encapsulation efficiency is far from expectation, especially for hydrophilic chemotherapeutic drugs. Besides, the intrinsic heterogeneity of EVs renders it difficult to evaluate drug encapsulation behaviour. Inspired by the active drug loading strategy of liposomal nanomedicines, here we report the development of a method, named "Sonication and Extrusion‐assisted Active Loading" (SEAL), for effective and stable drug encapsulation of EVs. Using doxorubicin‐loaded milk‐derived EVs (Dox‐mEVs) as the model system, sonication was applied to temporarily permeabilize the membrane, facilitating the influx of ammonium sulfate solution into the lumen to establish the transmembrane ion gradient essential for active loading. Along with extrusion to downsize large mEVs, homogenize particle size and reshape the nonspherical or multilamellar vesicles, SEAL showed around 10‐fold enhancement of drug encapsulation efficiency compared with passive loading. Single‐particle analysis by nano‐flow cytometry was further employed to reveal the heterogeneous encapsulation behaviour of Dox‐mEVs which would otherwise be overlooked by bulk‐based approaches. Correlation analysis between doxorubicin auto‐fluorescence and the fluorescence of a lipophilic dye DiD suggested that only the lipid‐enclosed particles were actively loadable. Meanwhile, immunofluorescence analysis revealed that more than 85% of the casein positive particles was doxorubicin free. These findings further inspired the development of the lipid‐probe‐ and immuno‐mediated magnetic isolation techniques to selectively remove the contaminants of non‐lipid enclosed particles and casein assemblies, respectively. Finally, the intracellular assessments confirmed the superior performance of SEAL‐prepared mEV formulations, and demonstrated the impact of encapsulation heterogeneity on therapeutic outcome. The as‐developed cargo‐loading approach and nano‐flow cytometry‐based characterization method will provide an instructive insight in the development of EV‐based delivery systems.